Palaeoclimatic and diagenetic controls based on clay mineralogy and organic matter distribution: The continental rift Cuyo Basin (Triassic), west‐central Argentina. Issue 7 (7th August 2022) - Salduondo, Joaquín; Comerio, Marcos; Pineda, Juan A.; Cravero, Fernanda; Erra, Georgina
Abstract: The Triassic Cuyo rift Basin is one of the renowned petroleum systems in South America that records distinctive alluvial, lacustrine and fluvial settings with volcanic input. The present study focuses on the clay mineral assemblages that represent the syn‐rift to post‐rift fills. Four clay mineral assemblages are defined based on X‐ray diffraction, optical and electron microscopy analyses. The illite/mica‐dominated assemblage is documented in the syn‐rift I (Cerro de las Cabras Formation). Such mineral phases are inherited and derived from the erosion of pre‐rift units, suggesting that physical weathering associated with a warm and semi‐arid climate played a leading role in their occurrence. Authigenic smectite clays are diagnostic in organic‐lean mudstones of the syn‐rift II (lower Potrerillos Formation) which point to alteration of pyroclastic material under a warm and semi‐arid to humid climate. A warm and humid climate prevailed during the deposition of lacustrine hydrocarbon source rocks (upper Potrerillos and Cacheuta formations). Organic‐rich mudstones show the illite/mica–kaolinite–smectite assemblage in conjunction with amorphous organic matter and restricted terrigenous elements. Diagenetic kaolinite booklets and bipyramidal quartz are attributed to the acidification of pore‐water related to kerogen transformation during burial diagenesis. Vitrinite reflectance values ( ca 0.63%) confirm that organic‐rich sediments reached the earliest oil window; however, smectite is devoid of illite layers throughout the Triassic succession, probably related to the absence of potassium in the system and the high crystallinity of the smectite, which delayed the transformation of smectite into mixed layers illite–smectite. Red mudstones of the post‐rift II (the fluvial‐lacustrine Rio Blanco Formation) show the kaolinite‐dominated assemblage where the authigenic kaolinite is interpreted to be derived from the alteration of volcaniclastic detritus and indicative of warm climate with markedly wet periods.